Apoe isoforms in patients with psoriasis - Ferreira, J.C.P. (2014)
Introduction: Psoriasis is a chronic inflammatory skin disease affecting 2–3% of the world population. Patients with psoriasis (Ps) have higher prevalence of lipid disorders when compared to unaffected individuals. These patients, especially those with severe and prolonged disease, have an increased morbidity and mortality from cardiovascular events. Apolipoprotein E (ApoE), a protein involved in lipid metabolism, cholesterol and phospholipid transport, has functionally relevant gene variants. It has been described that the e4 allele may increase the risk to develop atherosclerosis, and the e2 allele has been associated with hyperlipoproteinemia type III. An increased risk of psoriasis among persons with these two alleles has also been reported. Nevertheless, the role of ApoE in Psoriasis remains controversial. Objectives: The aim of this work was to investigate the relationship between APOE-e2/e3/e4 variants and psoriasis in a Portuguese population. Materials and Methods: A cohort of 178 unrelated (74 females, 104 males) severe psoriatic patients [according to the Psoriasis Area and Severity Index (PASI)] from Centro Hospitalar do Porto/Hospital de Santo Ant onio and 285 ethnically-matched healthy controls were studied. Genotyping of APOE was performed using a Polymerase chain reaction restriction fragment-length polymorphism (PCR-RFLP) assay. Results: The frequency of the e4 allele was significantly higher in patients than in controls [(11.5% vs. 7.6%), p = 0.044, OR=1.57 (1.01–2.45)]. Conclusion: The ApoE e4 isoform could be a risk factor for psoriatic disease in this population. Our result is in agreement with previous studies in a Spanish population that associated the e4 isoform with severe psoriasis. These results support the hypothesis that ApoE has a modulatory role in inflammatory conditions.